A kinetic approach to textural changes of different banana gentoypes (Musa sp.) cooked in boiling water in relation to stach gelatinization - Gibert, Olivier; Giraldo, A.; Ucles-Santos, JR; Sánchez, T.; Fernández, A.; Bohuon, P; Reynes, M; González, A.; Pain, JP; Dufour, D.L. (Elsevier, 2010)
A standardized textural test was developed for characterizing the banana pulp softening process during boiling. While a correlation was established between initial dry matter content and firmness, we observed large differences in cooking behavior between varieties and genotypes, with various softening rates and equilibrium retainable firmnesses. After 33-min cooking, some genotypes exhibited firmnesses 7 times higher than the softest. The biggest firmness losses relative to initial textures found after cooking were: FHIA 20 (20-fold) and FHIA 18 genotypes (40-fold) after 2 h, and Guineo (100-fold) after 98 min. The extent of starch gelatinization was investigated by differential scanning calorimetry and correlated to the amylographic maximum slope using rapid visco analyzer. Regardless of water uptake, the first 15-min cooking demonstrated a strong contribution by the gelatinization process to thermal softening. The firmness losses of 15 Colombian cultivated dessert and cooking banana varieties were evaluated using fractional conversion, and were best fitted by a first-order reaction (R2 ? 0.98). Multiple regression was shown to be suitable for preliminary cooking time prediction using Musaceae flour amylographic properties. At 30-min cooking, firmness evaluation was shown to be sufficient for identifying genotypic behavior, and therefore for predicting consumer preferences.